To the problem of using multimedia technologies in English language teaching. - Zhanetta Romaniuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
This article deals with the application of a wide range of multimedia technologies in teaching and learning foreign languages.  It reveals three main areas to be used for the expansion of cognitive abilities of students. First is the use of presentations. The main tool for making presentations is "Power Point" program. The second area is the application of multimedia capabilities of the Internet. Basically, the following resources are considered:  "Album" (scrapbook), the "Treasure Hunt", the problem statement (subject sampler), a list of  subject references (hotlist), forum. The third area represented in the article contains an analysis of blogs technology in teaching and learning the English language. This section describes different types of blogs, showing the blogs potential in the increase of computer literacy and proficiency in English. From the above analysis we can conclude that the multimedia technologies in education are used inefficiently. Using the computer should not be something artificial. It has to become an integral part of the educational process. The use of computer technologies in education is expanding horizons, enables to learn the discipline better, promotes students' interest in learning, generates creativity, spatial and logical thinking, imagination, observation and certain scientific skills.